Why is it so hard?: Unsilencing EFL undergraduate students experiences in the supervisory process - Mukhlash Abrar; Failasofah Failasofah; Luxvhyona Fharadhylla Prapassel; Liubov Darzhinova; Akhmad Habibi (Universitas Syiah Kuala, 2025)
The study aims to comprehensively explore thesis supervision from EFL undergraduate students perspectives. To be more specific, the present study investigates the challenges faced by EFL students and the strategies they used to overcome them while under thesis supervision. To meet the purposes of this study, a qualitative research design with a case study approach was used. Data were collected from 10 final-year students using in-depth interviews and audio recording techniques. The results drawn from the thematic analysis (Braun Clarke, 2006) indicates that EFL undergraduate students faced both internal and external challenges. Internal challenges included students lack of motivation, lack of confidence, and poor time management, whereas external challenges were insufficient support from supervisors, supervisors harsh feedback and comments, change of supervisor, and the internet and technology problems. In terms of overcoming strategies, the students mainly utilized the three strategies to cope with their challenges in the process of thesis supervision: 1) self-management (managing the study, self-study, maintaining positive motivation, doing positive and enjoyable activities, and being proactive), 2) academic and peer support (supervisor support, lecturer support, and peer support), and 3) technological support (language application, referencing application, and search for stable connection). These results suggest that the issues pertaining to thesis supervision warrant more attention and have a major influence on students progress in completing theses.